Structure and Optical Properties of Al-Doped ZnO Nanodrums as Anti-Reflection Coating Material in Solar Cells - Putri Luthfiana Sari; Hanik Munawaroh; Sayekti Wahyuningsih; Ari Handono Ramelan (Universitas Gadjah Mada, 2020)
Al-doped ZnO (AZO) nanodrums were synthesized using hydrothermal method at 80 °C for 20 h using precursor Zn(CH3COO)2·2H2O and Al(OH)(CH3COO)2 as a dopant by varying the addition of Al concentrations in the range of 0, 1, 5, 10, 15, and 20 mM. The variation of Al can affect structure properties, optical properties and the crystal growths of ZnO. Addition of Al can inhibit the crystal growth with the decrease of the crystal size ranging from about 43.46 to 37.21 nm. Morphology of Al variation doped ZnO of Al was studied using a Scanning Electron Microscope (SEM) and Transmission Electron Microscope (TEM) and showed nanodrums morphology. Optical properties of thin film AZO was evaluated using UV-Visible spectrophotometer. The transmission spectra showed that AZO has 85% transparency in the visible spectra with a sharp peak in the UV region. AZO with the addition of 20 mM Al has the largest transmittance and the lowest reflectance. The crystallite size of AZO can affect optical properties with the occurrence of blue shift. The thin film with transparent properties is a good candidate for application in the dye-sensitized solar cells, such as anti-reflecting coating. AZO was prepared as anti-reflection on the DSSCs system. The best efficiency of DSSCs performance was examined by varying the thickness of the layers of AZO and pointed an efficiency improvement up to 18.29 times.